High safety margins to drought‐induced hydraulic failure found in five pasture grasses. (31st March 2022) - Jacob, Vinod; Choat, Brendan; Churchill, Amber C.; Zhang, Haiyang; Barton, Craig V. M.; Krishnananthaselvan, Arjunan; Post, Alison K.; Power, Sally A.; Medlyn, Belinda E.; Tissue, David T.
Abstract: Determining the relationship between reductions in stomatal conductance ( g s ) and leaf water transport during dehydration is key to understanding plant drought responses. While numerous studies have analysed the hydraulic function of woody species, minimal research has been conducted on grasses. Here, we sought to characterize hydraulic vulnerability in five widely‐occurring pasture grasses (including both C3 and C4 grasses) and determine whether reductions in g s and leaf hydraulic conductance ( K leaf ) during dehydration could be attributed to xylem embolism. Using the optical vulnerability (OV) technique, we found that all species were highly resistant to xylem embolism when compared to other herbaceous angiosperms, with 50% xylem embolism ( P X50 ) occurring at xylem pressures ranging from −4.4 to −6.1 MPa. We observed similar reductions in g s and K leaf under mild water stress for all species, occurring well before P X50 . The onset of xylem embolism ( P X12 ) occurred consistently after stomatal closure and 90% reduction of K leaf . Our results suggest that factors other than xylem embolism are responsible for the majority of reductions in g s and K leaf during drought and reductions in the productivity of pasture species under moderate drought may not be driven by embolism. Summary Statement: Pasture grasses are highly resistant to xylem cavitation, with cavitation occurring consistently after significant reductions in stomatal conductance (gs ) and leaf hydraulic conductance ( K leaf ). Our results suggest that factors other than xylem cavitation are responsible for reductions in gs and K leaf during moderate drought with cavitation only occurring under extreme drought conditions.